Cuidados de enfermería post operatorios a pacientes de mas-tectomía por cáncer: revisión sistemática - Parra Ochoa, Joel Sebastián (2025)
Introduction: Breast cancer is one of the main causes of mortality in women with mastectomy being a common treatment. This surgery involves the partial or total removal of breast tissue to eliminate the tumor and prevent its spread. Risk factors such as genetic mutations, hormonal changes, and lifestyles influence its develop-ment. The post-surgical complications include infections, pain, and lymphedema, making nursing care essential for optimizing recovery. Objective: to describe nurs-ing care for post-mastectomy patients through a systematic review. Methodology: Qualitative, descriptive research based on a systematic review of nursing care for post-operative mastectomy patients with breast cancer. Finally, twenty relevant doc-uments were included. Results: The reviewed studies which included 9 articles on mastectomy and 11 on post-operative nursing care emphasizing the importance of comprehensive and personalized care. Discussion: the analyzed studies highlight the importance of self-care, education, and emotional support provided by the nurs-ing staff during post-operative recovery. A multidisciplinary approach and effective pain management are crucial in preventing complications such as infections and lymphedema. The Nursing Care Systematization (SAE) and the use of educational technologies are key strategies to improve patient self-care. Conclusions: Post-operative nursing care must be holistic, addressing both physical and emotional as-pects. The SAE and emotional support are essential for a successful recovery and improving the quality of life after mastectomy.